2011
DOI: 10.1258/shorts.2011.010108
|View full text |Cite
|
Sign up to set email alerts
|

Emergency thoracic surgery in elderly patients

Abstract: ObjectivesEmergency thoracic surgery in the elderly represents an extreme situation for both the surgeon and patient. The lack of an adequate patient history as well as the inability to optimize any co-morbidities, which are the result of the emergent situation, are the cause of increased morbidity and mortality. We evaluated the outcome and prognostic factors for this selected group of patients.DesignRetrospective chart review.SettingAcademic tertiary care referral center.ParticipantsEmergency patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Limmer ve ark. [24] kronik sistemik hastalığı olan ve acil ameliyat uygulanan hastalarda hastanede kalış süresinin uzadığını ve ameliyat sonrası mortalitenin arttığını bildirmişlerdir. Yazarlar ayrıca komorbiditenin prognoza etkisi değerlendirilir-ken; koroner arter hastalığı veya romatoid artritin, renal yetmezlik veya KOAH ile karşılaştırılamayacağını, fakat yine de sistemik hastalıkların tümünün mortalite ve morbidite artışına neden olduğunu bildirmişlerdir.…”
Section: Discussionunclassified
“…Limmer ve ark. [24] kronik sistemik hastalığı olan ve acil ameliyat uygulanan hastalarda hastanede kalış süresinin uzadığını ve ameliyat sonrası mortalitenin arttığını bildirmişlerdir. Yazarlar ayrıca komorbiditenin prognoza etkisi değerlendirilir-ken; koroner arter hastalığı veya romatoid artritin, renal yetmezlik veya KOAH ile karşılaştırılamayacağını, fakat yine de sistemik hastalıkların tümünün mortalite ve morbidite artışına neden olduğunu bildirmişlerdir.…”
Section: Discussionunclassified
“…15 In the vascular literature, severe chronic renal insufficiency has been associated with increased risks of death and diminished long-term survival after abdominal aortic aneurysm repair and lower extremity vascular reconstruction. [16][17][18][19][20] Rigdon et al found that patients with severe chronic renal insufficiency are at significantly greater risk than others for postoperative stroke and death after carotid endarterectomy, and they attributed these findings to difficulty controlling hypertension. 21 Sarac and associates also found that renal insufficiency was a predictor of 30-day mortality in patients with ruptured abdominal aortic aneurysms and a predictor of decreased long-term survival.…”
Section: Discussionmentioning
confidence: 99%